2022
DOI: 10.1111/acps.13420
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and treatment outcomes during mood‐stabilising treatment with lithium or quetiapine among outpatients with bipolar disorder

Abstract: Background Childhood trauma affects the course of mood disorders. Researchers are now considering childhood trauma as an influential factor in the treatment of mood disorders. However, the role of childhood trauma in the treatment of bipolar disorder remains understudied. Methods The effect of childhood trauma on treatment outcomes was evaluated among participants randomised to treatment with lithium or quetiapine in the Clinical and Health Outcomes Initiatives in Comparative Effectiveness for Bipolar Disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Elmer et al [ 196 ] reported that ketamine metabolite (2R,6R)-hydroxynorketamine reversed behavioral despair produced by adolescent trauma. Furthermore, recently, Wrobel et al [ 197 ] examined the role of childhood trauma in treating bipolar disorder. The effect of childhood trauma on treatment outcomes was evaluated among participants randomized to treatment with lithium or quetiapine.…”
Section: Discussionmentioning
confidence: 99%
“…Elmer et al [ 196 ] reported that ketamine metabolite (2R,6R)-hydroxynorketamine reversed behavioral despair produced by adolescent trauma. Furthermore, recently, Wrobel et al [ 197 ] examined the role of childhood trauma in treating bipolar disorder. The effect of childhood trauma on treatment outcomes was evaluated among participants randomized to treatment with lithium or quetiapine.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with BD who have a history of childhood trauma report more depressive episodes and experience more severe depressive symptoms, than individuals without a history of childhood trauma 6,17 . Interestingly, in other clinical populations (e.g., major depressive disorder) associations between childhood trauma and the experience of specific domains of depressive symptoms have also been highlighted 18–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Early-life stress, including childhood trauma, can disturb the development of the brain and thus increase the risk of mental illness [ 8 ]. It was found that BD patients with childhood trauma showed greater symptom severity [ 9 ], and increased risk of nonsuicidal self-injury [ 10 ]. Wrobel et al reported that depressive symptoms in BD patients were positively associated with childhood trauma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%